2018
DOI: 10.1177/1473325018766708
|View full text |Cite
|
Sign up to set email alerts
|

An autoethnography of a neurotypical adoptive mother’s journey through adoption into the world(s) of intellectual variety in the early years of the U.S. Education System

Abstract: This narrative is my story of being catapulted from a distanced space of relative naïveté and unknowing about the lives and challenges that children with disabilities face in the school system. It is also a tale about my increased radicalization birthed from witnessing my daughter’s school experiences and the informal social relations of childhood. Mine is one of many stories that could be told about this set of experiences. Taking an evocative, autoethnographic approach, and blending the evocative and analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The lack of educational resources was exacerbated by communication barriers. It was difficult for parents in this case to report educational resources needed by CWD ( 57 , 92 ). Parents of CWD also reported that the absence of teachers supporting the child-initiated activities and mentoring the progress of CWD education also constituted barriers ( 75 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The lack of educational resources was exacerbated by communication barriers. It was difficult for parents in this case to report educational resources needed by CWD ( 57 , 92 ). Parents of CWD also reported that the absence of teachers supporting the child-initiated activities and mentoring the progress of CWD education also constituted barriers ( 75 ).…”
Section: Resultsmentioning
confidence: 98%
“…The support and relationships section in (ICF Chapter 3) includes teachers, parents, relatives, and friends who provide physical or emotional support, nurturing, protection, help, and support to others at home, at work, in school, or at other sites where daily activities take place ( 36 ). Thirty studies highlighted barriers to education as a result of a lack of support and relationship development at school, in the family, and in the community ( 14 , 47 50 , 52 , 53 , 56 , 57 , 60 , 61 , 63 , 65 68 , 69 , 72 , 74 , 75 , 76 , 78 , 80 , 83 , 84 , 88 , 90 – 92 , 95 ).…”
Section: Resultsmentioning
confidence: 99%
“…My internship journey was indeed emotional, varyingly pleasant and disheartening, but compared to some autoethnographies (e.g. Comerford, 2019; Prasad, 2014) it does not concern a deeply personal experience, which should reduce the risk of own integrity damage. Of course, it up to the reader to reflect, also critically, on my story, including possible shortcomings and mistakes from my side.…”
Section: An Autoethnographic Approachmentioning
confidence: 91%
“…These employ a range of methods including poetry (Gallardo et al, 2009; Karki, 2016; Oehlers, 2017; Szto et al, 2005), diarising (Gant, 2017), letter writing (Oehlers, 2017), vignettes (Charles and Johns, 2023; Newcomb et al, 2022; Schmid, 2022), case studies (Gupta, 2017a; Hudson and Richardson, 2016), photovoice (Kattari and Beltrán, 2022), photography (Szto et al, 2005), collaborative (Malorni et al, 2022; Newcomb et al, 2022; Oswald et al, 2022; Sloane and Haas, 2020), and duoethnography (Wagaman and Sanchez, 2017). A narrative approach is commonly used within autoethnography (Comerford, 2019; Gant, 2017; Phillips, 2007, 2019; Schmid, 2010), although the discussion of method within articles varies. Fixsen (2023) provides a detailed discussion of authoethnographic methodology and key critiques.…”
Section: Autoethnographymentioning
confidence: 99%